Teacher Preparation and Development of Learning Methods Based Classroom Management - Nufus, Hayati; Abd Muhith; Moh Sutomo (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
Teaching and learning activities can be effective if the class is conducive, and this cannot be separated from the role of a teacher in managing the type. Teachers must pay attention to classroom management both personally and physically. This article aims to determine what a teacher must prepare to develop teaching methods with a class management approach at Madrasah Tsanawiyah Negeri 09 Jember Regency. This study uses a descriptive qualitative approach in collecting data using observation techniques, interviews, and documentation. The validation technique uses source triangulation, namely testing the credibility of the data, which is carried out by examining the data obtained using several sources. The research results conclude The teacher's preparation for learning is that the seating arrangements are carried out in various ways, such as traditional shapes, semicircular shapes, or the letter U and group shapes. The teacher adjusts the student's sitting position. The development of the learning method implemented is 1) The Market Place Activities learning method developed by the teacher can arouse enthusiasm/increase learning enthusiasm. 2) the Expert Group method can grow students' courage to express their opinions in class. 3) the Group Investigation method can cultivate good work habits in everyday life.